Overview of the Centrifugal Visual System in Mammalian Species - Vereczki, Viktória; Csáki, Ágnes; Köves, Katalin (Highlights on Medicine and Medical Science Vol. 1, 2021)
It is well established that there is a bidirectional neuronal connection between the retina and the central nervous system. The retinofugal connection is composed of the classical visual system and the retinohypothalamic tract. The retinopetal connections are composed of several subsystems. These pathways, coming from different structures of the central nervous system, are called together: centrifugal visual system. The structures, where the centrifugal visual system originates from, are located in the forebrain and brainstem. The centrifugal visual fibers through the optic nerve enter the optic nerve layer of the retina. Some fibers terminate on the ganglion cells. Others via the inner plexiform layer reach the inner nuclear layer and terminate on the amacrine and displaced ganglion cells. Several neuropeptides and neurotransmitters were recognized in the cells of origin of the centrifugal visual system. The function of the subsystems is very different. It strongly depends on the structure where the fibers come from.